Adaptive Multimedia Retrieval. Large-Scale Multimedia Retrieval and Evaluation 9th International Workshop, AMR 2011, Barcelona, Spain, July 18-19, 2011, Revised Selected Papers - Detyniecki, Marcin; García-Serrano, Ana; Nürnberger, Andreas; Stober, Sebastian (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This book constitutes the refereed post-proceedings of the 9th International Conference on Adaptive Multimedia Retrieval, AMR 2011, held in Barcelona, Spain, in July 2011. The 9 revised full papers and the invited contribution presented were carefully reviewed and selected from numerous submissions. The papers cover topics ranging from theoretical work to practical implementations and its evaluation, most of them dealing with audio or music media. They are organized in topical sections on evaluation and user studies, audio and music, image retrieval, and similarity and music.